TEACHING ENGLISH THROUGH SONG LYRICS TO IMPROVE SPEAKING SKILLS AT THE STUDENT OF SMP TAKHASSUS AL- QUR’AN IN SAINS DORMITORY - Kusriyah, Ainun Jariyah Dewi; Sahid, Sahid (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2025)
This study aims to improve students' speaking skills through the use of English song lyrics at SMP Takhassus Al-Quran in Sains Dormitory. It focuses on three aspects of speaking skills: fluency, pronunciation, and expression. The research employs a classroom action research design conducted in two cycles, consisting of planning, action, observation, and reflection. The findings indicate that using English song lyrics creates a fun and interactive learning environment. Students become more motivated, enthusiastic, and confident in speaking English. Activities such as singing along, discussing song meanings, and practicing pronunciation support their language development. However, challenges such as complex vocabulary, unusual pronunciations, and varying student ability levels require special attention from the teacher. Despite these challenges, students’ speaking skills improve significantly, as shown by increased test scores from pre-test to post-test II. Therefore, English song lyrics are considered an effective method for enhancing speaking skills and fostering motivation in learning English.